Assessment of apoptosis and appearance of hepatocyte growth factor in placenta at different gestational ages: A cross-sectional study - Ilze Kreicberga; Anna Junga; Māra Pilmane (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Fetal growth is determined by the interaction between mother and fetus using the placental interface throughout the pregnancy. Objective: To research apoptosis and appearance of hepatocyte growth factor (HGF) in placentas of different gestational ages and to describe the anthropometrical and clinical indices of mothers and newborns. Materials and Methods: The study material was obtained from 53 human immunodeficiency virus negative pregnant women of legal age without systemic diseases. The staining of placental apoptotic cells was processed by a standard in situ cell death detection kit. The detection of HGF was provided by the ImmunoCruz goat ABC Staining System protocol sc-2023. Relative distribution of positive structures was evaluated using the semiquantitative counting method. Results: The mean rank value of the amount of HGF-containing cells (cytotrophoblasts, syncytiotrophoblasts, extravillous trophoblasts, Höfbauer cells, and cells of extraembryonic mesoderm) was 1.61 ± 0.94. Apoptotic cells (cytotrophoblasts, syncytiotrophoblasts, extravillous trophoblasts, and cells of extraembryonic mesoderm) were found in all placental samples of various gestational ages (term 13.00 ± 13.05 and preterm 27.00 ± 18.25); in general, their amount decreased with advancing gestational age of the placenta (p < 0.01). Conclusion: Weight of a placenta directly depends on the gestational age and correlates with the main fetal anthropometrical parameters (weight, length, and head and chest circumferences). The decrease in HGF-containing and apoptotic cells with advancing gestation depends on the adaptation potential of the placenta, proving the other ways of cellular disposition.